Adoption Of Improved Pig Rearing Practices In Andhra Predesh - latha, P.Asha; Prabhakar, K. (Indian Journal of Veterinary Sciences and Biotechnology, 2012)
The present study was carried out on 95 farmers distributed under semi - urban (37) and rural areas (58) belonging to four mandals of Krishna district in AndhraPredesh..Study revealed that several farmers maintained their pigs according to their socio -economic status and knowledge level.There was a marked improvement in adoption of scientific pig rearing practices with respect to breeding ,feeding, disease control, management both in semi-urban and rural areas after the scientific adoption.
Keywords: Pigs; Scientific Rearing; Adoption